Paul (2017)
PAUL is a Colombian brand of modular backpacks for university students. This brand stems from the need to respond to different questions and gaps within the backpack market regarding the balance between the functional and the aesthetic aspect. In addition, PAUL responds to a brand storytelling and lifestyle that aims to highlight the differentiating aspect of the product. The design process developed and explained in this document is based mostly on the methodologies, processes and frames presented in Vijay Kumar's '101 Design Methods'- Other methodologies and frames will be referenced in due course.--Tomado del Formato de Documento de Grado.